Influence of Chloramine-T on the Thermodynamics of Clouding Behaviour of Non-Ionic Surfactant Triton X-100 - Patil, A.A.; Patil, T.J. (Asian Journal of Chemistry, 2010)
The phenomenon of solubilization of nonionic surfactant Triton X-100 has been studied through the influence of additive chloramine-T in aqueous medium by measuring the cloud points of the pure surfactant and with chloramine-T. The cloud points of pure surfactant found to be declined with increased concentration of Triton X-100. The cloud points of mixed system show increasing trends with increased chloramine-T. This is mainly due to increased micelle concentrations. The influence of chloramine-T on the cloud point of Triton X-100 is a clear indication that the phenomenon of clouding is associated with the different micelles coalescing. Considering cloud point as threshold temperature of the solubility, the thermodynamic parameters of clouding process (DGºcl, DHºcl and DSºcl) have been evaluated using "phase separation model". The phase separation results from micelle-micelle interaction. It is found that the overall clouding process is exothermic and DHºcl > TDSºcl indicating that the process of clouding is guided by both enthalpy and entropy. This work supports the conjecture that the clouding is critical phenomenon rather than the growth of micelles. Findings of the present work supports to made the probable evidence of electrolyte surfactant interactions in aqueous medium.